Desenvolvimento de teste rápido para diagnóstico de Hantavirose humana - Guimarães, João Pedro Tôrres (2017)
Human Hantavirosis is a serious lung disease caused by Hantavírus, pathogen that is related mainly with wild rodents, insectivorous animals and small mammals (shrews, moles and bats). In humans, the disease is called Hantavírus Cardiopulmonary Syndrome (HCPS), which has high mortality rates (~ 50%). In Brazil, 1,871 cases of HCPS have been confirmed, with 789 deaths between the years 1993 to 2016. The symptoms in humans are not very characteristic in the initial stage, and very similar to diseases such as Dengue and Yellow Fever, making it difficult to diagnose, with a need of fast and accurate diagnostic methods for Hantaviruses. To assist in the diagnosis of Hantavírus, we aim to develop a quick and simple test based on immunochromatography. This paper presents results obtained with 3 prototypes of tests compoused by a nitrocellulose membrane (NC) impregnated in the form of a line with the recombinant nucleocapsid protein (rN) Hantavírus-specific, as the capture agent and another parallel line impregnated with protein A, as reaction control. In the NC edges we have a sample zone composed of cellulose fiber and a glass microfiber tape containing the anti-IgM antibodies and / or anti-human IgG conjugated to colloidal gold and at the other end an absorption zone composed of cellulose fiber. We evaluated 163 samples, among them, positive serum for Hantavírus, Dengue, Mayaro, Oropouche, Yellow fever, Malaria (P. falciparum) Malaria (P. vivax), Parvovirus B19, Rubella, HIV, Chikungunya and samples from health donors. After several evaluations, the prototype for the detection of IgM and IgG simultaneously, using the C concentration of protein rN, cutoff point 1 and reading time of the results of 10 minutes was chosen, presenting 100% sensitivity, 99, 3% specificity, 90.9% VPP and 100% VPN. It is expected that the product of this study helps in the diagnosis of severe cases of Hantavírus improving the prognosis of patients and reducing the high rates of HCPS fatality, moreover, helping to promote health by conducting epidemiological studies thereby promoting the construction of strategies to prevent Hantavírus infection.